National Defense College of the Philippines Library collection evaluation through collection mapping and conspectus approach - De Castro, Rachel Ann D. (2009)
The National Defense College of the Philippines (NDCP) is the highest educational institution in the country dedicated to the conduct of advanced programs in national security administration. Its library is comprised with 3138 volumes of reference books, magazines, periodicals, research works of students and other studies by the staff, faculty and consultants of the College.